In celebration of James Alfred Loader's sixtieth birthday (12 July 1945 - 12 July 2005) - Spangenberg, Izak J. J. (Old Testament essays, 2005)
Extracted from text ... In honour of James Alfred Loader OTE 18/2 (2005), 165-171 165 In celebration of James Alfred Loader's sixtieth birthday (12 July 1945 - 12 July 2005) Any student who studied Old and/or New Testament at a university in South Africa during the seventies and eighties of the previous century could not but take note of the publications of four eminent biblical scholars - Ferdinand Deist, Jimmie Loader, Riempies Prinsloo and Willem Vorster. They were our 'Four Musketeers' and we enjoyed their company and scholarship. Sadly three of them passed away during the nineties. The only one who remained is Jimmie ..